Pengaruh Gaya Kepemimpinan Transformasional, Pengembangan Karir dan Budaya Organisasi Terhadap Kinerja Karyawan - Noviherni; Novianti, Dea (LPPM STIE PPI, 2023)
Introduction/Main Objectives: To test whether there is an influence of transformational leadership style, career development, and organizational culture on employee performance. Background Problems: The performance of employees in the company is not achieving the targets that have been set so that it becomes and hinders the company's performance. Novelty: Re-testing the same variables by previous researchers, with different research locations. Research Methods: This research uses primary data by distributing questionnaires to 50 respondents in the marketing division taken using the non-probability sampling technique, namely the saturated sample, meaning that all populations are used as samples and data analysis using the SPSS version 25 program. Finding/Results: There is a significant influence in improving employee performance, namely by increasing the dominant organizational culture then by carrying out career development which is carried out continuously. Conclusion: Employee performance can be influenced by Transformational Leadership Style, Career Development and Organizational Culture with a value of 85.5% and 14.5% by other variables.